STRATEGI PEMASARAN PADA PRODUK TABUNGAN UNTUK MENINGKATKAN JUMLAH NASABAH PENABUNG DI BANK SYARIAH - Alma Tita Assyfa; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
This paper discusses marketing strategies for Islamic bank savings products to increase the number of depositors. Islamic banks, operating based on sharia principles, provide services without charging interest, which is considered haram in Islam. The key to success in increasing the customer base lies in marketing strategies, particularly the marketing mix (7P), which includes product, price, place, promotion, people, physical evidence, and process. Effective marketing strategies not only attract more customers but also improve the bank’s competitiveness, profits, and customer satisfaction. The research methodology used is descriptive qualitative, relying on interviews and direct observations. The results indicate that customers are drawn to factors such as product availability (with ATM features) and strategic bank locations, while promotions and pricing have less significant effects on their decisions to save. This highlights the importance of strategic product and service development, considering customer preferences and behavior to boost savings numbers. Overall, a well-executed marketing mix positively influences depositors' decisions.